Theoretical foundations of the problem of pedagogical creativity (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the analysis of the phenomenon ofpedagogical creativity as one of the basic determinants of the creativedevelopment of the individual. Various psychological and pedagogical ideasconcerning the essence, content and specifics of pedagogical creativity areconsidered. The article describes the structure and main stages of creativityimplementation in the pedagogical process. The article asserts the presenceof algorithmic and creative components in pedagogical creativity, whichmakes it possible to master creativity both at the objective and subjectivelevels.
Keywords: creativity; pedagogical creativity; creative pedagogical activity; features of pedagogical creativity